Perbandingan Potensi Daun Ketepeng dan Minyak Ikan Lemuru sebagai Agensia Reduksi Metan dalam Memperbaiki Kualitas Pakan Ternak Ruminansia - Susi Dwi Widyawati (Universitas Sebelas Maret (UNS), 2009)
The research was done to study the potential of ketepeng leaf meal and lemuru fish oil as agents to reduce methane production. The composition of feed supplements, lamtoro leave meal (LLM), urea (U) and mollases (M) were in different ratios: 1:5, 1:6 and 1:7 and ketepeng leaf meal (DKM) and lemuru fish oil (MIL). The feed supplement was added to the native grass as a basal diet, P1: U: M = 1:5, DKM, P2: U: M = 1:5, MIL, P3: U: M = 1:6, DKM, P4: U: M = 1:6, MIL, P5: U: M = 1:7, DKM, P6: U: M = 1:7, MIL. Research was done with in vitro gas technique. Inoculum was taken from rumen fluid of a fistulated male cow, which was taken before feeding in the morning. Rumen fluid pH did not significantly different, indicating the microbial fermentation in rumen run well and normally were not affected by the treatment. The VFA production of P5 and P6 was significantly lower than P1, P2, P3 and P4 (P <0.05). Production of C2 and C3 were relatively the same except for P6 (P <0.05) which relative higher. Ratio of C2/C3 and inversely related C3, when C3 production increased the C2/C3 ratio decreased (P <0.05). Methane production of P6 was higher but did not different with P4 and P5. It can be concluded that diet which produced low methane was the native grass supplemented with urea and molases at ratio 1: 5 contained either ketepeng leaf meal or lemuru fish oil. Key words: native grass, supplement, ketepeng leaf meal, lemuru fish oil, methane production.